My life in the PLO : the inside story of the Palestinian struggle - Ḥūt, Shafīq (Pluto Press, 2011)
This is the inside story of the Palestine Liberation Organisation (PLO), from its beginnings in 1964 to the signing of the Oslo agreement in 1993. For over three decades, the main goal of the PLO was to achieve a just peace in the Arab-Israeli conflict, and to build a democratic state in Palestine for all its citizens. Shafiq Al-Hout, a high ranking PLO official until his resignation in 1993, provides previously unavailable details on the key events in its history such as its recognition by the UN and the Oslo peace negotiations. Taking us right to the heart of the decision making processes, this book explains the personalities and internal politics that shaped the PLO's actions and the Palestinian experience of the twentieth century. Although he was an insider, Al-Hout's book does not shy from analysing and criticising decisions and individuals, including Yasser Arafat. This book is an essential piece of history that sheds new light on the significance of the PLO in the Palestinian struggle for justice. -- Publisher description.